STIGMA DAN DISKRIMINASI PADA ANAK DENGAN HIV AIDS (ADHA) DI SEPULUH KABUPATEN/KOTA DI INDONESIA - Sugiharti Sugiharti; Rini Sasanti Handayani; Heny Lestary; Mujiati Mujiati; Andi Leny Susyanti (Puslitbang Upaya Kesehatan Masyarakat, 2019)
Abstract Background: Children with HIV are vulnerable groups that need to be protected, considering that their parents have often died of HIV/AIDS. Objective: The purpose is to find information about stigma and discrimination against children with HIV/AIDS in 10 districts in Indonesia. Method: The study was conducted in 2015 with a cross-sectional research design using quantitative and qualitative combined approaches (mixed methods approaches). Quantitative study respondents were parents/guardians of children with HIV/AIDS aged ≥18 months totaling 201 children with HIV/AIDS. The variables studied included: age, child status, children with HIV/AIDS companion and source of transmission), reasons for closing the ADHA status and reasons for opening status. The qualitative study informants were doctors, nurses, case managers, NGOs, and the Education Office Results: Quantitative results showed that 41.8% of children with HIV/AIDS were aged 4-9 years; 58.5% are in school; 61.7% of children with HIV/AIDS companions are biological parents; 91.5% of sources of transmission are from biological mothers; 57.5% of reasons for closing status because of shame/stigma/ discrimination, 45.9% of reasons for opening status because the family already knew. Qualitative results of stigma and discrimination occur in families, the environment, schools, and health services Conclusion: Children with HIV/AIDS are a vulnerable group that must be protected. They have the right to live properly and safely like other children. But the results of this study found that there was still stigma and discrimination for Children with HIV/AIDS, both in the home, school and health care facilities. Key words: Children with HIV/AIDS, Stigma and Discrimination, HIV/AIDS Abstrak Latar belakang: Anak dengan HIV merupakan kelompok rentan yang perlu dilindungi, mengingat orang tua mereka sering kali sudah meninggal karena HIV/AIDS. Tujuan: mengetahui gambaran stigma dan diskriminasi pada Anak dengan HIV/AIDS (ADHA) pada 10 Kabupaten/Kota di Indonesia. Metode: Penelitian dilakukan tahun 2015 dengan disain potong lintang, menggunakan pendekatan kuantitatif dan kualitatif (mixed methods approaches). Responden studi kuantitatif adalah orangtua/wali dengan ADHA berusia ≥18 bulan sejumlah 201 ADHA yang diperoleh dari Dinas Kesehatan. Variabel yang diteliti meliputi: usia, status anak, pendamping ADHA dan sumber penularan), alasan menutup status ADHA dan alasan membuka status. Informan studi kualitatif adalah adalah dokter, perawat, manajer kasus, LSM, dan Dinas Pendidikan Hasil: Hasil kuantitatif menunjukkan 41,8% ADHA di usia 4–9 tahun; 58,5% berstatus sekolah; 61,7% pendamping ADHA adalah orangtua kandung; 91,5% sumber penularan berasal dari ibu kandung; 57,5% alasan menutup status karena malu/stigma/diskriminasi, 45,9% alasan membuka status karena keluarga sudah tahu. Hasil kualitatif bahwa stigma/ diskriminasi terjadi di keluarga, lingkungan sekitar, sekolah dan pelayanan kesehatan. Kesimpulan: ADHA merupakan kelompok rentan yang harus dilindungi. Mereka berhak untuk dapat hidup dengan layak dan aman seperti anak – anak lainnya. Namun hasil penelitian ini menemukan masih terjadi stigma dan diskriminasi bagi ADHA, baik di lingkungan rumah, sekolah, maupun fasilitas pelayanan kesehatan. Kata kunci: ADHA, Stigma dan Diskriminasi, HIV-AIDS